A new tool for network analysis on team sports - Silva, Frutuoso (2019)
Network analysis has been used to classify the interactions between teammates in team sports. However, no dedicated software or application was specifically developed to import, compute and export data in the specific case of sports, as far as we know. Based on that, we intend to propose a new application to visualize and analyze networks in soccer. The Ultimate Performance Analysis Tool (uPATO) allows observing, codifying, importing, visualizing, computing measures and exporting data from the observed games. The user may use a single application to work in the visualization and analysis of the match only considering the network that emerges from the game. In this paper it will be possible to observe the steps to visualize and import data and it will also be described the development of some network measures to characterize the centralities and general properties of unweighted and weighted graphs and digraphs. Finally, data from a real game will be used to test the network measures implemented and to show the values that can be exported and interpreted.